1998
DOI: 10.1890/1051-0761(1998)8[s72:itppif]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Precautionary Principle in Fisheries Management Through Marine Reserves

Abstract: Abstract. Overexploitation of marine fisheries remains a serious problem worldwide, even for many fisheries that have been intensively managed by coastal nations. Many factors have contributed to these system failures. Here we discuss the implications of persistent, irreducible scientific uncertainty pertaining to marine ecosystems. When combined with typical levels of uncontrollability of catches and incidental mortality, this uncertainty probably implies that traditional approaches to fisheries management wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
252
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(266 citation statements)
references
References 9 publications
10
252
0
4
Order By: Relevance
“…Identification and mapping of EFH constitute an area of active research by fishery biologists (Benaka 1999). In addition, marine reserves and closure of fishing areas have been proposed for conservation of exploited fish stocks (Clark 1996;Ogden 1997;Roberts 1997;Allison et al 1998;Guenette et al 1998;Lauck et al 1998). The establishment of EFH and marine reserves and the accurate estimation of spawning stock biomass require knowledge of the location of spawning and nursery areas for fishes.…”
mentioning
confidence: 99%
“…Identification and mapping of EFH constitute an area of active research by fishery biologists (Benaka 1999). In addition, marine reserves and closure of fishing areas have been proposed for conservation of exploited fish stocks (Clark 1996;Ogden 1997;Roberts 1997;Allison et al 1998;Guenette et al 1998;Lauck et al 1998). The establishment of EFH and marine reserves and the accurate estimation of spawning stock biomass require knowledge of the location of spawning and nursery areas for fishes.…”
mentioning
confidence: 99%
“…It has been hypothesised that marine reserves could insure against environmental shocks, or function as a "hedge against inevitable management limitations" (Lauck et al 1998). Sumaila (2002) applied a Beverton-Holt bioeconomic simulation model and found that the implementation of a reserve may indeed protect discounted economic rent.…”
Section: Uncertaintymentioning
confidence: 99%
“…Marine reserves, to the extent that they protect fish stocks from depletion and enhance their recovery, also should be looked to as important research opportunities (e.g. Alcala & Russ 1990, Lauck et al 1998). …”
Section: Effects Of Human Exploitationmentioning
confidence: 99%